Peningkatan Perilaku Asertif Remaja: Mixed-Method - Rachmawati, Ajeng; Hariastuti, Retno Tri; Christiana, Elisabeth (Universitas Sebelas Maret, 2025)
Adolescence is marked by strong desires and increased vulnerability to peer influence. During this developmental stage, adolescents frequently imitate peer behaviors, resulting in both beneficial and detrimental outcomes. Insufficient assertive behavior skills heighten the risk of engagement in negative activities, ranging from minor infractions such as truancy, tardiness, and classroom passivity to more severe issues, including drug use, online gambling, dating, violence, brawls, cheating, intimidation, and suicide. This study seeks to identify the concept of assertiveness as defined in previous research, examine strategies to enhance it, and explore school counselors' experiences in supporting students' assertiveness. The research employs a mixed-method approach, specifically a Sequential Exploratory Qualitative Design, integrating a literature review and phenomenological study. The literature review follows four analytical stages: data collection, data categorization, data display, and conclusion drawing. Subsequently, a phenomenological study is conducted through in-depth interviews with five school counselors to investigate guidance and counseling interventions aimed at improving student assertiveness. The findings indicate that assertiveness fosters positive behaviors, strengthens the capacity to address social challenges, reduces aggressiveness, and helps prevent substance abuse. Therefore, it is recommended that school counselors implement both behavioristic and cognitive interventions to promote assertive behavior among adolescents.